Home-literacy environments and language development in toddlers with Down syndrome - Dulin, Madison S.; Loveall, Susan J.; Mattie, Laura J. (Frontiers in Psychology, 2023)
Introduction The present study aimed to (1) characterize the home-literacy environments (HLE) of toddlers with Down syndrome (DS) and (2) examine if richness of the HLE, child engagement during shared storybook reading activities, quality of a caregiver-child shared storybook reading activity, and exposure to language in the home environment predicted child receptive vocabulary concurrently (Time 1) and 6 months later (Time 2). Methods Participants were toddlers with DS (n = 13 at Time 1, 11–29 months of age; n = 10 at Time 2) and their mothers. Mothers completed a Home Literacy Environment Questionnaire at Time 1, which was used to characterize the HLE and to calculate two composite variables: richness of the HLE and child engagement in shared storybook reading. Also at Time 1, the home language environment was measured using adult word count from the LENA Recorder DLP©. The LENA was also used to audio-record and capture the quality of a caregiver-child storybook reading task in the child’s home using the book Dear Zoo. At both time points, mothers completed the MacArthur-Bates Communicative Development Inventories, and the number of words understood variable was used to measure receptive vocabulary. Results/Discussion Results indicated that toddlers with DS experience rich HLEs and interactive shared storybook reading encounters with their mothers. A multiple linear regression revealed that child engagement and the home language environment correlated with both toddlers’ concurrent and later receptive vocabularies, while the richness of the HLE and the shared storybook reading task emerged as moderate predictors of receptive vocabulary 6 months later.